2009
DOI: 10.1542/peds.2008-0586
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Newborn Screening: Outcome in Screened and Unscreened Patients at Age 6 Years

Abstract: Screening by tandem mass spectrometry provides a better outcome for patients at 6 years of age, with fewer deaths and fewer clinically significant disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(105 citation statements)
references
References 23 publications
8
88
0
7
Order By: Relevance
“…This finding could be replicated in our follow-up study. As for many other conditions, also in MCADD the number of patients identified by screening is higher than the number of patients identified clinically (Derks et al 2005;Wilcken et al 2007;Wilcken et al 2009). The genotypic spectrum in screened cohorts includes presumably mild mutations like c.199T>C (Andresen et al 2001;Maier et al 2005), and there is ongoing discussion about genotype-phenotype correlation.…”
Section: Discussionmentioning
confidence: 93%
“…This finding could be replicated in our follow-up study. As for many other conditions, also in MCADD the number of patients identified by screening is higher than the number of patients identified clinically (Derks et al 2005;Wilcken et al 2007;Wilcken et al 2009). The genotypic spectrum in screened cohorts includes presumably mild mutations like c.199T>C (Andresen et al 2001;Maier et al 2005), and there is ongoing discussion about genotype-phenotype correlation.…”
Section: Discussionmentioning
confidence: 93%
“…The outcome of MCAD deficiency is generally favorable if the disorder is identified early, treatment is implemented, and prompt interventions occur during times of illness. 22,23 Medical management strategies include avoidance of medium-chain triglycerides, frequent feeding to shorten periods of fasting, and prompt medical attention during conditions of increased metabolic demand such as infection.…”
Section: Discussionmentioning
confidence: 99%
“…It may be assumed that individuals with the mild phenotype identified by NBS may remain asymptomatic throughout their lives [30]. This hypothesis is supported by family studies identifying asymptomatic individuals with biochemical evidence of IVA and genotypes identical to their younger siblings identified by NBS [30] and by the reported increase in the prevalence of organic acidurias in screened cohorts as compared to clinical ascertainment [32,37,48,66,67].…”
Section: Clinical Presentationmentioning
confidence: 97%
“…Prevalences from other countries were reported to be lower, such as 1 in 660,000 in Taiwan [46] or 1 in 105,000 in Portugal [47]. In Australia, the prevalence of IVA has been shown to be 1 in 775,600 in the unscreened population and 1 in 230,750 in a screened cohort [48]. Similarly, an analysis of available evidence by Dionisi-Vici et al showed a more than four times higher incidence of IVA in the screened population as compared to clinical diagnosis [37], suggesting that the phenotypic spectrum of IVA detected by NBS is different and may include individuals that would not have presented clinically.…”
Section: Iva Newborn Screening: Diagnosis Birth Prevalence and Diffementioning
confidence: 99%